Effects of the Multi-channel Problem Solving Therapy Program on Repeated Suicide Risk among Psychiatric Patients Hospitalized in a Psychiatric Hospital - Bubpawan, Anotai; Skulphan, Sombat; Wannachaiyakul, Saranya (Journal of The Royal Thai Army Nurses, 2026)
This quasi-experimental research aimed to examine the effect of a multi-channel problem solving therapy program on repeated suicide risk among psychiatric patients in a psychiatric hospital. The sample consisted of 32 male and female psychiatric patients. Specifically selected one is Khonkaen Rajanagarindra Psychiatric hospital. All individuals were inpatients at psychiatric hospitals under the Department of Mental Health, Ministry of Public Health, with 16 in the experimental group and 16 in the control group. Data were collected using a personal information questionnaire and the Mini International Neuropsychiatric Interview (M.I.N.I) for suicide risk assessment. Data analysis was performed using comparative statistics, one-way ANOVA with repeated measures, and independent t-tests.The results showed that: The mean scores for repeated suicide attempt risk of psychiatric patients after receiving the Multi-channel Problem Solving Therapy Program were significantly lower at the 1-month and 3-month follow-up than at baseline, at the .05 level. The result of this study suggest that this program can be applied to care of psychiatric patient to reduce the risk of repeated suicide. For the sustainability of the result, further study should be extended to a longer period, such as 6 months or 1 year.